Survey paper on intrusion detection techniques - Kulhare, Rachna; Singh, Dr. Divakar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Network security has been one of the mostÂ important problems in Computer Network Management and Intrusion is the most publicized threats to security. In recent years, intrusion detection has emerged as an important field for network security. IDSs obtain better results when each class of attacks is treated as a separate problem and handled by specialized algorithms. Now in days various model and method are available for intrusion detection. In this paper, we present a study of intrusion detection. Detection method to improve the detection rate & helping the users to develop secure information systems.